Pengaruh Kepercayaan Dan Kepuasan Terhadap Loyalitas Nasabah Tabungan Harapan BCA Cabang Ambon - Simson Melmambessy; Eline O. Hutubessy; Stevanus Johan Gomies (Jurnal Administrasi Terapan, 2024)
This research aims to analyze the influence of customer trust and satisfaction on the loyalty of "Tabungan Harapan" savings customers at PT Bank BCA Ambon Branch. The study adopts a quantitative approach, using a survey method to collect data from "Tabungan Harapan" customers at the BCA Ambon Branch. The quantitative approach was chosen because it is suitable for measuring the relationships between the research variables, namely trust, satisfaction, and customer loyalty. This research utilizes a descriptive and explanatory research design. The descriptive design is used to provide an overview of the levels of trust, satisfaction, and loyalty among "Tabungan Harapan" customers at BCA Ambon Branch. The explanatory design is employed to analyze the influence of trust and satisfaction on customer loyalty. The population in this study consists of all active "Tabungan Harapan" customers at BCA Ambon Branch. The sampling technique used is purposive sampling, where the sample is selected based on specific criteria. The total sample size used in this study is 115 respondents. Multiple regression analysis was conducted to test the influence of the independent variables (trust and satisfaction) on the dependent variable (customer loyalty). The regression analysis results show that trust (X1) has a regression coefficient of 0.320 with a p-value of 0.010, which is less than 0.05. Satisfaction (X2) also significantly affects customer loyalty, with a regression coefficient of 0.144 and a p-value of 0.020 (p < 0.05). The F-test results indicate that the overall regression model is significant, with an F-statistic value of 4.058 and a p-value of less than 0.002. Trust has a greater influence on customer loyalty compared to satisfaction.Keywords: customer trust, customer satisfaction, customer loyalty